Situation and distribution of bovine brucellosis in the province of Formosa, Argentina - Elias, Iris C. (2023)
The aim of this study was to update the epidemiological information of brucellosis in the province of Formosa, Argentina, based on records from the Research and Transfer Centre during the 2018-2021 period. In total, 151 218 samples of bovine sera from 1953 establishments in the province of Formosa were serologically analysed. Data analysis was done using logistic regression. The presence of spatial association clusters for populations with heterogeneous distribution was evaluated by scanning a data group less than 50% of the population at risk. The distribution of herds positive for brucellosis was assumed as a Bernoulli distribution. The prevalence of bovine brucellosis was 0.88%, while that of herds positive for brucellosis was 17.1%. The intra-herd prevalence was 5.73% (95% CI 0.34-24.18%). In 2018, a prevalence of 0.44% was observed with increases in 2019 (1.77%) and 2021 (0.52%). The spatial analysis identified four significant clusters, two of them with a higher risk of developing the disease and two with a lower risk, presenting Relative Risk (RR) values of 3.92, 30.13, 0.02 and 0.014, respectively. The disease continues to be present in the province with high prevalence, concentrating in the central and eastern areas of the province of Formosa.